IgA dominant glomerulonephritis associated to staphylococcus infection: a peculiar case report - Pestana, Nicole (2019)
IgA dominant glomerulonephritis associated to Staphylococcus infection is a rare clinical entity that has been described mainly in case reports. Biopsy features can resemble other disease entities mainly IgA nephropathy and Henoch‑Schönlein purpura nephritis. Treatment of IgA dominant glomerulonephritis associated to staphylococcal infection is based on antibiotics for the underlying infection, controlling hypertension and edema and may resort to concomitant use of steroids in selected cases. Prognosis markers such as hypertension, diabetes and interstitial fibrosis may influence treatment as they are associated with poor renal outcomes. We report a case of a 63‑year‑old man with known hypertension, pre‑diabetes and recent history of methicillin‐sensitive staphylococcus aureus bacteremia associated to prostatitis, who presented with a one‑month history of edema, arthralgia and foamy urine. Over this period he progressed to anasarca and nephrotic range proteinuria with concomitant rise in creatinine levels being documented. The renal biopsy showed segmental endocapillary proliferation and IgA segmental dominant staining associated to C3 and lambda in minor distribution. On completion of two months of steroid therapy the patient partially recovered his renal function and proteinuria. After nine months of tapering steroids, he presented with acute inflammatory arthritis supporting an inflammatory background disease. To our knowledge this case describes an unusual entity such as IgA dominant glomerulonephritis associated to staphylococcal infection co‑presenting with an associated reactive arthritis.